Peer-Review Guidelines Promoting Replicability and Transparency in Psychological Science. Issue 4 (December 2018) - Davis, William E.; Giner-Sorolla, Roger; Lindsay, D. Stephen; Lougheed, Jessica P.; Makel, Matthew C.; Meier, Matt E.; Sun, Jessie; Vaughn, Leigh Ann; Zelenski, John M.
More and more psychological researchers have come to appreciate the perils of common but poorly justified research practices and are rethinking commonly held standards for evaluating research. As this methodological reform expresses itself in psychological research, peer reviewers of such work must also adapt their practices to remain relevant. Reviewers of journal submissions wield considerable power to promote methodological reform, and thereby contribute to the advancement of a more robust psychological literature. We describe concrete practices that reviewers can use to encourage transparency, intellectual humility, and more valid assessments of the methods and statistics reported in articles.